A Critique of English for the Students of Engineering - Mohammad Hadi Mahmoodi (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
Textbook evaluation is one of the important steps in developing instructional materials process. The present article evaluates and criticizes the book English for the Students of Engineering (Atai, Zare Alanagh, Nasiri, Taherkhani & Iranmehr, 2016), which belongs to the new generation of English for specific purposes (ESP) textbooks. To this end, the textbook evaluation model proposed by Mahmoodi and Ahmadisafa (2014) was used. This model is specifically designed for evaluating ESP books. This study showed that this book, in contrast to previous ESP books developed by SAMT, has higher technical qualities and conforms to scientific theories and experimental findings in the field of TEFL. However, besides its advantages, this book suffers from some weak points which are discussed below.